Effects of cooking methods on total isothiocyanate yield from cruciferous vegetables. Issue 10 (9th September 2020) - Wang, Zinian; Kwan, Marilyn L.; Pratt, Rachel; Roh, Janise M.; Kushi, Lawrence H.; Danforth, Kim N.; Zhang, Yuesheng; Ambrosone, Christine B.; Tang, Li
Abstract: Cruciferous vegetables are primary sources of dietary isothiocyanates (ITCs), a group of phytochemicals showing promising cancer‐chemopreventive activities in multiple cancer models. However, no study has thoroughly examined how cooking affects the yields of ITCs from cruciferous vegetables. In this study, a high‐performance liquid chromatography (HPLC)‐based cyclocondensation assay was performed to examine the ITC yields from four major cruciferous vegetables (broccoli, cabbage, cauliflower, and kale) under six cooking conditions (stir‐frying, steaming, microwaving, boiling, stewing, and chip‐baking for kale only) and measured the level of ITCs under the raw condition for a comprehensive list of cruciferous vegetables and ITC‐containing condiments. A wide range of ITC yields was found across vegetables and condiments. Cooking significantly altered the ITC yields, showing an averagely four‐fold increase by lightly cooking (stir‐frying, steaming, and microwaving) and a 58% decrease by heavily cooking (boiling, stewing, and chip‐baking). These findings will provide the evidence‐based cooking guidance on cruciferous vegetable consumption and help better estimate dietary ITC exposure in epidemiologic studies. Abstract : Cooking significantly altered the isothiocyanate yields, showing an averagely four‐fold increase by lightly cooking (stir‐frying, steaming, and microwaving) and a 58% decrease by heavily cooking (boiling, stewing, and chip‐baking).